2020
DOI: 10.1075/jicb.18016.san
|View full text |Cite
|
Sign up to set email alerts
|

Mapping lecturer questions and their pedagogical goals in Spanish- andEnglish-medium instruction

Abstract: This article explores the relationship between teacher questioning practices and pedagogical objectives in Spanish- and English-medium lectures. The results obtained from the analysis of 16 lectures delivered by the same two university teachers both in Spanish and English reveal that the use of questions could be exploited more effectively for pedagogical purposes. Consequently, this paper tries to raise teachers’ awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Although current teaching methodologies are aimed at fostering more egalitarian roles in classroom participation, the teacher still holds the upper hand when it comes not only to organizing and leading the classroom but also to distributing the floor (Hu & Li, 2017;Sánchez-García, 2020;Teo, 2016). Larson and Lovelace (2015) observed that instructors attempted to engage their students by regularly asking questions in lecture-based science classes at a large public research university in the United States.…”
Section: Complexity and Questioning Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although current teaching methodologies are aimed at fostering more egalitarian roles in classroom participation, the teacher still holds the upper hand when it comes not only to organizing and leading the classroom but also to distributing the floor (Hu & Li, 2017;Sánchez-García, 2020;Teo, 2016). Larson and Lovelace (2015) observed that instructors attempted to engage their students by regularly asking questions in lecture-based science classes at a large public research university in the United States.…”
Section: Complexity and Questioning Practicesmentioning
confidence: 99%
“…In this vein, underscore that previous studies have revealed that local EMI teachers often lack the necessary linguistic proficiency to engage their students in interaction. Despite these limitations, teachers tend to dominate the interaction and the low level of students' participation is more often than not conditioned by teachers' questioning practices Macaro & Childs, 2021;Sánchez-García, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…That lecturers would have different views on English as a medium of instruction (EMI) is not surprising since its pedagogical benefits as a medium of instruction have not been fully established by research yet (Dearden, 2015). Its effectiveness as a medium for learning depends on factors like the availability of interaction opportunities in the classroom, the alignment of interactions with the intended pedagogical goals (Sánchez-García, 2020), the ability of the students to express themselves in English (Lo & Macaro, 2015), and it also depends on the role of students' first language in EMI (Nashaat-Sobhy, 2017). Another point of concern some lecturers may have is deciding which variety or register of English to use in their EMI classrooms (for more on this point, see Young & Walsh, 2010).…”
Section: Journal For the Psychology Of Language Learningmentioning
confidence: 99%
“…(iii) The bulk of research has been in mathematics (see [11] for a systematic review of 15 studies; [12]), business administration [13], and science classrooms [1,3,[14][15][16], while few papers have dealt with humanities, as is the case of the present study.…”
Section: Introductionmentioning
confidence: 99%